Genetics of Growth Disorders—Which Patients Require Genetic Testing? - Argente, Jesús; Tatton-Brown, Katrina; Lehwalder, Dagmar; Pfäffle, Roland (Frontiers in Endocrinology, 2019)
The second 360° European Meeting on Growth Hormone Disorders was held in Barcelona, Spain, in June 2017, with the aim of examining various aspects of clinical conditions involving growth and endocrine disorders. The Merck KGaA (Darmstadt, Germany) Global Medical Affairs-funded meeting included sessions entitled ‘Pragmatism vs Curiosity in Genetic Diagnosis of Growth disorders’ and ‘Adherence Triangle in Management of Growth Disorders’. The sessions each had three presentations, followed by a discussion period, and are reported as manuscripts authored by the speakers. The first session examined current concepts of genetics and growth in the clinical setting, in terms of both growth failure and overgrowth. For patients with short stature, multiple genes have now been identified that result in growth hormone deficiency, which may be isolated or associated with additional pituitary hormone deficiencies, or in growth hormone resistance, primary IGFALS deficiency, insulin-like growth factor-I deficiency, insulin-like growth factor-II deficiency, insulin-like growth factor-I resistance and primary PAPP-A2 deficiency. In patients with overgrowth in combination with an intellectual disability (OGID), two predominant gene families, the epigenetic regulator genes and PI3K/AKT pathway genes, have now been identified. Specific processes should be followed for decisions on which patients require genetic testing and which genes should be examined for anomalies. The decision to carry out genetic testing should be directed by the clinical process, and not be merely for research purposes. The intention of genetic testing should be to direct the clinical therapy for improvement of the growth disorder.